2021
DOI: 10.1021/acs.chemrestox.0c00422
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans Model Studies Show MPP+ Is a Simple Member of a Large Group of Related Potent Dopaminergic Toxins

Abstract: Although the causes of Parkinson’s disease (PD) are not fully understood, the consensus is that a combination of genetic and environmental factors plays a major role. The discovery that the synthetic chemical, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-derived N-methyl-4-phenylpyridinium (MPP+), recapitulates major pathophysiological characteristics of PD in humans and other mammals has provided the strongest support for this possibility; however, several key aspects of the mechanism remain unclear. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In the hepatic mitochondrial proteome, alterations in the abundance of proteins related to pathways of neurodegeneration were observed. A majority among these were multiple subunit components of respiratory Complex I, which is theorized to be to particularly susceptible to proteopathic damage 92 , 94 , 95 and is the target of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, MPTP, a neurotoxin which results in a PD-like syndrome in people 96 , and used to model PD in rodents, and its analogues 43 , 97 99 .…”
Section: Discussionmentioning
confidence: 99%
“…In the hepatic mitochondrial proteome, alterations in the abundance of proteins related to pathways of neurodegeneration were observed. A majority among these were multiple subunit components of respiratory Complex I, which is theorized to be to particularly susceptible to proteopathic damage 92 , 94 , 95 and is the target of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, MPTP, a neurotoxin which results in a PD-like syndrome in people 96 , and used to model PD in rodents, and its analogues 43 , 97 99 .…”
Section: Discussionmentioning
confidence: 99%
“…Aluminium is a toxic metal ubiquitously present on earth that impairs mitochondrial bioenergetics and leads to cognitive disorder once it enters the brain [ 36 ]. Moreover, it has been found that N-methyl-4-phenylpyridinium (MPP + ) related compounds are dopaminergic toxins that can induce mitochondrial oxidative stress and dysfunction [ 37 ]. Thus, they are usually used to induce animal models of PD.…”
Section: Induction Of Neurotoxicitymentioning
confidence: 99%